Lipid Perfluorohexane Nanoemulsion Hybrid for MRI-Guided High-Intensity Focused Ultrasound Therapy of Tumors - Liu, Sitong; Hou, Xiuqi; Zhu, Wenjian; Zhang, Fang; Chen, Weiling; Yang, Binjian; Luo, Xin; Wu, Dalin; Cao, Zhong (Frontiers in Bioengineering and Biotechnology, 2022)
Magnetic resonance imaging-guided high-intensity focused ultrasound (MRI-guided HIFU) is a non-invasive agent of diagnosis and treatment. Because of its non-invasive characteristic, MRI-guided HIFU is applicable in tumor ablation. This study prepared a multifunctional nanotheranostic agent (SSPN) for MRI-guided HIFU ablation of tumors. The agent was prepared by loading perfluorohexane (PFH) and superparamagnetic iron oxides (SPIOs) in silica lipid. Perfluorohexane was introduced to improve the ablation effect of HIFU and the ultrasound (US) contrast performance. This is due to its liquid-to-gas transition characteristic that makes it sensitive to temperature. Superparamagnetic iron oxides (SPIOs) were used as MRI contrast agent. Silica lipid was selected because it is a more stable carrier material compared with normal lipid. Previous studies have shown that SSPNs have good biocompatibility, stability, imaging and therapeutic effects. Therefore, this system is expected to develop an important therapeutic agent for MRI-guided HIFU therapy against tumors.